Production of natural antioxidants from vegetable oil deodorizer distillates: Effect of catalytic hydrogenation - Pagani, María Ayelén (2009)
Natural tocopherols are one of the main types of antioxidants found in living creatures, but they also have other critical biological functions. The biopotency of natural (+)alfa-tocopherol (RRR) is 36% higher than that of the synthetic racemic mixture and 300% higher than the SRR stereoisomer. Vegetable oil deodorizer distillates (DD) are an excellent source of natural tocopherols. Catalytic hydrogenation of DD preconcentrates has been suggested as a feasible route for recovery of tocopherols in high yield. However, it is important to know whether the hydrogenation operation, as applied to these tocopherol-rich mixtures, is capable of preserving the chiral (RRR) character, which is critical to its biopotency.(+)alfa-tocopherol enriched sunflower oil and methyl stearate, as well as sunflower oil DD, were fully hydrogenated using commercial Ni and Pd catalysts (120?180 C; 20?60 psig). Products were analyzed by chiral HPLC. Results show that the desired chiral configuration (RRR) is fully retained. Thus, the hydrogenation route can be safely considered as a valid alternative for increasing the efficiency of tocopherol recovery processes from DDs while preserving their natural characteristics.